Management of purple blotch (Alternaria porri) disease of garlic (Allium sativum L.) - R P Gupta, R C Gupta, N K Pandey, (Journal of Spices and Aromatic Crops, 2014)
Field trials were conducted for the management of purple blotch disease of garlic during Rabi 2008–11. Six fungicides viz., tebuconazole @ 0.1%, azoxystrobin @ 0.1%, hexaconazole @ 0.1%, sectin (fenamidone + mancozeb) @ 0.2%, propineb @ 0.2% and mancozeb @ 0.25% and a control formed the treatments. The pooled data of three years indicated that purple blotch incidence ranged from 10% to 33.33% and intensity from 0.44% to 4.71%. Significantly lower incidence (21.11%) as well as intensity (1.78%) were recorded with spray of mancozeb @ 0.25% followed by tebuconazole @ 0.1% and azoxystrobin @ 0.1%. The highest gross yield (86.49 q ha-1) and marketable yield (86.07 q ha-1) were also recorded with spray of mancozeb @ 0.25% followed by azoxystrobin @ 0.1% and tebuconazole @ 0.1%. It was evident from the data that 1.73% intensity with 21.11% incidence of purple blotch at 45 days after planting (DAP) caused economic yield losses and it is considered as threshold value of purple blotch in garlic. The higher incidence (33.33%) and intensity (4.71%) of the disease as well as lowest gross yield (62.18 q ha-1) and marketable yield (61.87 q ha-1) were recorded in untreated control. The present study revealed that contact fungicide mancozeb and systemic fungicides namely tebuconazole and azoxystrobin spray after 30 DAP and subsequent sprays at fortnightly intervals were ideal for the management of purple blotch disease and increased garlic yield.